Influence of organic and inorganic sources of fertilizers on growth, yield and economics of fennel (Foeniculum vulgare Mill.) cultivation under semi arid conditions - G Lal, R Singh, A S Godara, U S Gupta, (Journal of Spices and Aromatic Crops, 2014)
The experiment was conducted with eight treatments (absolute control and varying proportions of organic and inorganic sources of nutrients viz., 100% recommended dose of nitrogen (RDN) through fertilizers (90:45:0), 100% RDN through farm yard manure, 100% RDN through poultry manure, 100% RDN through vermicompost, 50% RDN through fertilizers + 50% RDN through farm yard manure, 50% RDN through fertilizers + 50% RDN through poultry manure and 50% RDN through fertilizers + 50% RDN through vermicompost). Results revealed that RDN through fertilizers and combinations of different organic and inorganic sources produced significantly higher grain yield over absolute control. RDN (100%) applied through fertilizers exhibited highest vegetative growth and yield attributes with maximum yield (2325 kg ha-1), net returns (Rs. 62,091 ha-1) and benefit cost ratio (3.01), closely followed by 50% RDN through fertilizers + 50% RDN through vermicompost.